PENGEMBANGAN LANDING PAGE PRODUK SUPLEMEN BERBASIS WEB MENGGUNAKAN AGILE SCRUM - Ramadhani Pambudhi, Raden Muhammad Syaikhan; Kunaefi, Anang; Permadi, Andhy (JURSIMA, 2025)
This research aims to develop an effective and responsive landing page to increase awareness and sales conversion of probiotic-prebiotic supplement products. In the competitive supplement industry, an attractive and informative landing page is key to differentiating products and encouraging consumers to make purchases. This research uses the Scrum method to develop the landing page iteratively, with a focus on testing and collecting user feedback to ensure an optimal user experience. This research is expected to support digital marketing strategies and increase the conversion of Milk Supplement Products.